Genetic evidence for the interaction between Bacillus anthracis-encoded phage receptors and their cognate phage-encoded receptor binding proteins - Forrest, Samantha; Ton, Sarah; Sholes, Samantha L.; Harrison, Sarah; Plaut, Roger D.; Verratti, Kathleen; Wittekind, Michael; Ettehadieh, Elham; Necciai, Bryan; Sozhamannan, Shanmuga; Grady, Sarah L. (Frontiers in Microbiology, 2023)
Bacteriophages such as γ and AP50c have been shown to infect strains of Bacillus anthracis with high specificity, and this feature has been exploited in the development of bacterial detection assays. To better understand the emergence of phage resistance, and thus the potential failure of such assays, it is important to identify the host and phage receptors necessary for attachment and entry. Using genetic approaches, the bacterial receptors of AP50c and  have been identified as Sap and GamR, respectively. A second AP50c-like phage, Wip1, also appears to use Sap as a receptor. In parallel with this work, the cognate phage-encoded receptor binding proteins (RBPs) have also been identified (Gp14 for , P28 for AP50c, and P23 for Wip1); however, the strength of evidence supporting these protein-protein interactions varies, necessitating additional investigation. Here, we present genetic evidence further supporting the interaction between Sap and the RBPs of AP50c and Wip1 using fluorescently tagged proteins and a panel of B. anthracis mutants. These results showed that the deletion of the sap gene, as well as the deletion of csaB, whose encoded protein anchors Sap to the bacterial S-layer, resulted in the loss of RBP binding. Binding could then be rescued by expressing these genes in trans. We also found that the RBP of the -like prophage Ba03 relied on CsaB activity for binding, possibly by a different mechanism. RBPBa03 binding to B. anthracis cells was also unique in that it was not ablated by heat inactivation of vegetative cells, suggesting that its receptor is still functional following incubation at 98°C. These results extend our understanding of the diverse attachment and entry strategies used by B. anthracis phages, enabling future assay development.